2017
DOI: 10.1002/jso.24549
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte to monocyte ratio and neutrophil to lymphocyte ratio are superior inflammation‐based predictors of recurrence in patients with hepatocellular carcinoma after hepatic resection

Abstract: Both LMR and NLR might be preferable independent prognostic factors for DFS in HCC patients undergoing hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 43 publications
(51 reference statements)
3
55
0
Order By: Relevance
“…Subsequently, 3 articles did not meet the inclusion criteria and were therefore excluded. Eventually, seven studies, comprising a total of 2,507 patients, were considered eligible for the present meta-analysis18242526272829. The PRISMA flow diagram of the study selection process was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 3 articles did not meet the inclusion criteria and were therefore excluded. Eventually, seven studies, comprising a total of 2,507 patients, were considered eligible for the present meta-analysis18242526272829. The PRISMA flow diagram of the study selection process was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(14)(15)(16) Moreover, the lymphocyte-to-monocyte ratio (LMR) predicts poor survival of patients with certain cancers including HCC. (17)(18)(19)(20)(21) However, we are unaware of any report that demonstrates the prognostic significance of the LMR for patients who underwent LT for HCC.…”
mentioning
confidence: 99%
“…However, previous studies just implemented univariate and/or multivariate analysis on account of unbalanced clinical parameters among groups with distinct outcomes, where over fitting is common because of covariate selection . In this regard, even multiple analysis might give rise to relatively unreliable results . Herein we performed PSM, for the first time, to examine the predictive impact of NLR of 90‐day mortality in our large scale cohort.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,9 In this regard, even multiple analysis might give rise to relatively unreliable results. 10 Herein we performed PSM, for the first time, to examine the predictive impact of NLR of 90-day mortality in our large scale cohort. We found that NLR > 8.9 was a favourable cut-off for identifying LC at high risk, controlling for the influences of potential confounders and selection bias after PSM.…”
Section: Discussionmentioning
confidence: 99%